Recommendations about the Use of Psychotropic Medications during the COVID-19 Pandemic - Andrade, Gabriela (2020)
Introduction: The COVID-19 pandemic is a particularly relevant threat to mentally ill patients, and it constitutes a new challenge for health care providers. To the best of our knowledge, there is not any embracing published review about the use of psychotropic drugs during the COVID-19 pandemic.Materials and Methods: Non-systematic literature review. A search in the PubMed database was performed, with the terms ‘psychotropic drugs’, ‘COVID-19’, ‘psychiatry’ and ‘pandemic’. Consensus and clinical guidelines about psychotropic drugs and COVID-19 approach, published by scientific societies, governmental entities and drug regulatory agencies were included.Results and Discussion: We present the recommendations about the use of psychotropic drugs during the COVID-19 pandemic, in the outpatient and inpatient settings. The treatment of affective bipolar disorder and schizophrenia have now added increased difficulties. Some psychotropic drugs interfere with the pathophysiology of the novel coronavirus infection and they could interact with the drugs used in the treatment of COVID-19. Some patients will need pharmacological interventions due to the presence of delirium. Smoking cessation changes the serum levels of some psychotropic drugs and may influence their use.Conclusion: The COVID-19 pandemic has created new challenges in clinical practice. Psychiatric patients are a vulnerable population and often a careful clinical, laboratorial and electrocardiographic evaluation may be needed, particularly in those diagnosed with COVID-19. The regular treatment of mentally ill patients with COVID-19 presents increased complexity.